Targeting unfolded protein response signaling pathways to ameliorate protein misfolding diseases - Ryno, Lisa M (Curr Opin Chem Biol, 2013)
Protein homeostasis (or proteostasis) within the endoplasmic reticulum (ER) is regulated by the unfolded protein response (UPR). The UPR consists of three integrated signaling pathways activated by the accumulation of misfolded proteins within the ER lumen. Activation of the UPR alters ER proteostasis through translational attenuation of new protein synthesis and transcriptional remodeling of ER proteostasis pathways, providing a mechanism to adapt ER proteostasis in response to cellular stress. The capacity of the UPR to alter ER proteostasis suggests that exogenous manipulation of UPR signaling pathways offers therapeutic promise to alter the fate of pathologic proteins associated with human protein misfolding diseases. Here, we discuss the therapeutic potential of exogenous UPR activation to treat human disease and highlight specific small molecule approaches for regulating UPR signaling that could be beneficial to treat protein misfolding diseases.